2023
DOI: 10.1159/000533173
|View full text |Cite
|
Sign up to set email alerts
|

The Good, the Bad, and the Serum Creatinine: Exploring the Effect of Muscle Mass and Nutrition

Silvia De Rosa,
Massimiliano Greco,
Michela Rauseo
et al.

Abstract: Muscle wasting (sarcopenia) is one of the hallmarks of critical illness. Patients admitted to intensive care unit develop sarcopenia through increased protein catabolism, a decrease in protein syntheses, or both. Among the factors known to promote wasting are chronic inflammation and cytokine imbalance, insulin resistance, hypermetabolism, and malnutrition. Moreover, muscle wasting, known to develop in chronic kidney disease patients, is a harmful consequence of numerous complications associated with deteriora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 84 publications
0
5
0
Order By: Relevance
“…An elevated serum creatinine level indicates impaired baseline renal function, which increases postoperative AKI risk 28 , 40 . However, serum creatinine levels may underestimate renal function impairment in populations with diminished muscle mass 41 , such as those suffering from sarcopenia or malnutrition. It has been demonstrated that these populations are at an increased risk of AKI 2 , 42 .…”
Section: Discussionmentioning
confidence: 99%
“…An elevated serum creatinine level indicates impaired baseline renal function, which increases postoperative AKI risk 28 , 40 . However, serum creatinine levels may underestimate renal function impairment in populations with diminished muscle mass 41 , such as those suffering from sarcopenia or malnutrition. It has been demonstrated that these populations are at an increased risk of AKI 2 , 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Calculation is based on Equation (1): where BW corresponds to body weight in kg, c 1 and c 2 are the first and second serum creatinine concentrations in mg/dL, respectively, P adj is the adjusted creatinine production in mg and CCR is the creatinine clearance in hundreds of mL per minute [ 20 ]. It must be noted that estimating creatinine clearance by measuring serum creatinine is not an optimal approach in the critically ill, as sarcopenia or a poor clinical status influence serum creatinine concentrations [ 31 ]. Furthermore, creatinine is not only filtered, but also secreted by the kidneys [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Total protein and creatinine have been identified as significant predictive factors for PPOLOS in lung cancer patients, a novel finding given the current scarcity of research on their predictive value in this context. Both creatinine and total protein are critical markers for assessing nutritional status, 36 , 37 with malnutrition known to be associated with increased mortality, compromised functional status, and extended hospital stays. 38 , 39 , 40 Consequently, the significance of preoperative nutritional management for lung cancer patients is increasingly recognized by oncology specialists as a means to enhance postoperative recovery and mitigate complications.…”
Section: Discussionmentioning
confidence: 99%